The Impact of Strategic Vigilance on E-management in the National Railway Transport Company (SNTF) - Kasmi Karima; Djalab Zohra (Journal of Information Technology Management)
This study aimed to identify the impact of strategic vigilance (SV)on the useful application of electronic management in the National Railway Transport Company (SNTR), and to achieve the objectives of the study; a survey was designed and distributed to a simple random sample of 200 individuals from the National Railway Transport Company (SNTR) ), From which 180 questionnaires were retrieved, The results obtained indicate Spanish the respondents' perception of both strategic vigilance with its dimensions (competitive vigilance and technological vigilance, commercial vigilance and environmental vigilance) and electronic management in the researched company, The findings also revealed positive effect of strategic vigilance in the practical application of electronic management in the company National Rail Transport (SNTR).